THE INFLUENCE OF REPRODUCTIVE HEALTH DISORDERS ON THE LIFE QUALITY OF MEN - Nataliya Medvedovska; Iryna Stovban (Acta Medica Leopoliensia)
The purpose of the publication is to conduct a medical and sociological study of changes in the quality of life components of men diagnosed with reproductive health disorders.